Seroprevalence of measles and rubella virus antibodies in the population of the Community of Madrid, 2008-2009 - Luis García-Comas; J.C. Sanz Moreno; M. Ordobás Gavín; D. Barranco Ordóñez; J. García Gutiérrez; B. Ramos Blázquez; I. Rodero Garduño (Elsevier, 2015)
Summary: The seroprevalence (SP) of measles and rubella virus antibodies is presented by age groups obtained in the IV Serosurvey of the Region of Madrid (2008-2009). The target population is composed of residents with ages ranging between 2 and 60 years in the Region of Madrid. A two-stage cluster sample is used. The SP of measles virus antibodies is 97.8% (CI 95%: 97.3-98.2). The highest SP is observed in the 2-5 year and 41-60 year age groups. The point estimate does not reach 95% in the 16-20 and 21-30 year age groups. The SP of rubella virus antibodies is 97.2% (CI 95%: 96.5-97.7). The SP is over 95% in all of the age groups. In immigrant women between the ages of 16 and 49, the SP is 95.9% (CI 95%: 93.7-97.4). The identification of groups susceptible to the measles virus in young adults could lead to outbreaks as a result of importing the virus. The circulation of the rubella virus is possible among immigrant women aged between 16 and 49 years, which could lead to the appearance of SRC cases. Epidemiological surveillance will allow the impact on the measles and rubella elimination plan to be determined in the future. Keywords: Measles, Rubella, Seroprevalence, Epidemiological surveillance, Population surveys